User Experience Evaluation of M-Passpor Using User Experience Questionnaire - Winanda, Salsa; Tengku Khairil Ahsyar; Angraini; Megawati (APIC, 2024)
This study evaluates UX of the M-Passpor application, an m-government application to facilitate the online passport administrative process and reduce queues at the immigration office. Although this application offers convenience in making passports, since its release M-Paspor has received many complaints from users regarding the services provided. A UX evaluation was conducted using the UEQ method, which measures six of these aspects aspects: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. The outputs presented that Perspective and Attractiveness aspects had the highest scores, indicating that the app is quite easy to understand and visually appealing. However, the Novelty aspect had a low score, indicating a lack of innovation and new experiences for users. Based on these findings, the researcher recommends improving efficiency, simplifying processes, notifications and feature innovation to improve UX. The outcome of this study is expected to become the basis for improving the UX quality of the M-Passpor application so as to create better and satisfying services for users in the future